MODEL OF CONSUMER TRUST ON TRAVEL AGENT ONLINE: ANALYSIS OF PERCEIVED USEFULNESS AND SECURITY ON RE-PURCHASE INTERESTS (CASE STUDY TIKET.COM) - Bimaruci, Hazimi; Agung Hudaya; Hapzi Ali (Dinasti International Journal of Economics, Finance & Accounting, 2020)
Technological development is very rapid, many things are very influential with the presence of the internet, many consumers are spoiled by online shopping, with this it will make it easier for transactions between sellers and buyers. Starting from the search for goods, to make payment transactions. But with the internet, in addition to making it easier for buyers and sellers, but also creating new problems, with the convenience, it will make it easier for competitors to do the same. Competitors will more easily seize customers, and customers will also more easily go to other sellers, therefore the question arises, how to make repurchase intention occur. One business player who sees the internet as a new market share in attracting consumers is the online travel agent business. In the beginning, this travel business was only done conventionally. Then the travel business also utilizes technology in marketing activities. With this research will find out whether there is an influence between perceived usefulness, with trust, then whether there is a perceived influence on repurchase intention, and whether there is an influence of trust with repurchase intention. The sampling technique was purposive sampling. Using the Slovin formula, a sample of 100 customers was obtained, the margin of error set was 10% or 0.10. Quantitative analysis methods with SEM analysis tools and Smart PLS and SPSS tools.